The struggle is real: a systematic review of food insecurity on post-secondary campuses - Bruening, Meg (J Acad Nutr Diet, 2017)
BACKGROUND: Numerous international studies have examined cross-sectional correlates of food insecurity (FI) among post-secondary students; a study is needed to synthesize the findings of this work to support vulnerable students. OBJECTIVE: To systematically review peer-reviewed and gray literature to assess the prevalence of FI on post-secondary institutions, as well as factors related to FI among students and suggested/practiced solutions. DESIGN: Systematic literature review. MEDLINE, Web of Science, and PsycINFO databases were searched for peer-reviewed literature for FI research; a Google search was conducted to obtain gray literature on FI among post-secondary students. PARTICIPANTS/SETTING: Undergraduate and graduate students at post-secondary institutions of higher education. MAIN OUTCOME MEASURES: Measures included 1) prevalence of FI; 2) socio-demographic, health, and academic factors related to FI; 3) solutions to address FI on post-secondary institutions. RESULTS: Seventeen peer-reviewed studies and 41 sources of gray literature were identified (out of 11,476 titles). All studies were cross-sectional. Rates of FI were high among students, with average rates across the gray and peer-reviewed literature of 35% and 42%, respectively. FI was consistently associated with financial independence, poor health and adverse academic outcomes. Suggested solutions to address food security among post-secondary institutions addressed all areas of the socio-ecological model, but the solutions most practiced included those in the intrapersonal, interpersonal, and institutional levels. CONCLUSIONS: FI is a major public health problem among post-secondary students. Studies are needed to assess the long-term impact of FI among this vulnerable population. More research is needed on the effectiveness of FI interventions.